1973
DOI: 10.1037/h0034735
|View full text |Cite
|
Sign up to set email alerts
|

Attention and processing capacity in auditory recognition.

Abstract: This research examined whether attention and processing capacity limitations affect the recognition of single tones. The 5s identified either one or both dimensions (loudness and quality) of a short test tone. Processing time was controlled by following the test tone with a masking tone after a variable silent interval. Performance improved with increases in the silent intertone interval, but was not affected by whether 5s identified one or both tone dimensions. These results indicated no capacity limitations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

1974
1974
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 15 publications
(15 reference statements)
0
17
1
Order By: Relevance
“…These results are in contrast to those in a recent experiment by Moore and Massaro (1973). In their experiment, Ss identified the loudness and quality of an auditory stimulus as well in the divided-attention condition as in the focused-attention condition.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…These results are in contrast to those in a recent experiment by Moore and Massaro (1973). In their experiment, Ss identified the loudness and quality of an auditory stimulus as well in the divided-attention condition as in the focused-attention condition.…”
contrasting
confidence: 56%
“…The general finding from these studies is that independent detection on these channels takes place, at least when only one signal is presented. Moore and Massaro (1973) have found that frequency and intensity of simple tones may be processed independently. Posner and Boies (1971) .rorr bunon sta ges-of-processing analysis to arrive at similar conclusions regarding the locus of attention.…”
mentioning
confidence: 99%
“…A technique that appears to control successfully amount of visual processing is that of using a visual mask (Moore & Massaro, 1973). This technique has been applied to the present context in a very recent study by Cantor and Thomas (1976).…”
Section: -----:-----=----mentioning
confidence: 99%
“…Within the 25Q-rnsec range of interstimulus intervals (ISIs) between target and mask that results in ABRM, accuracy of target identification generally improves as the lSI increases. This effect holds with pitch, timbre, lateralization, and loudness judgments (Hawkins & Presson, 1977;Massaro, 1970Massaro, , 1972Massaro, , 1975aMassaro, , 1975bMoore & Massaro, 1973). To explain these findings, Massaro and his colleagues suggested that as the lSI between target and backward mask increases, more time can be devoted to perceptual processing of the target and, as a result, recognition performance improves (Massaro, 1976;Kallman & Massaro, 1983;Massaro, 1975aMassaro, , 1975b.…”
mentioning
confidence: 99%